(untitled) (Tạp chí Y học Cộng đồng, 2025)
Objective: To investigate the current status of balance impairment in post-stroke patients. Methods: This study included 32 post-stroke patients who met all inclusion criteria and were undergoing treatment at Hai Duong Rehabilitation Hospital from January 2024 to July 2024. Participants were assessed by using the Berg Balance Test and clinical features (static and dynamic sitting balance, static and dynamic standing balance, range of motion, muscle tone). Results: Mostpost-stroke patients experienced balance issues with varying rates of: 53.1% high-level balance impairment, 40.6% moderate impairment, and only 6.3% intact balance. The primary impairment included standing balance, with 46.9% of participants presenting poor performance in both dynamic and static standing. Otherwise, sitting balance was less affected, with over 50% demonstrating normal or good balance. Conclusion: Balance should be assessed in all post-stroke patients. Early intervention for balance status to improve mobility and quality of life for stroke survivors significantly.